PEMIDANAAN PELAKU PINJAM NAMA PERUSAHAAN YANG MELAKUKAN TINDAK PIDANA KORUPSI DALAM PENGADAAN BARANG DAN JASA - Marsel Joy Kaliaga Ketaren (2022)
Borrowing company name is a phenomenon that often occurs in the process of procuring government goods/services, this action often results in business actors paying additional costs for borrowing from companies that do not belong to them, so these costs are often taken from the budget that has been provided by the government. So that in its implementation, flag borrowers will reduce various kinds of building materials in order to continue to benefit, so that the specifications requested are not in accordance with the agreement in the contract with the government so that state losses occur in the procurement process, the research method used in this study is normative juridical, namely legal research conducted by examining library materials or secondary data as the basic material for research. The result of this study is that there are not many laws and regulations in Indonesia that discuss flag borrowing, so there is no legal clarity whether this practice is actually prohibited or not, in the case of flag borrowers who commit criminal acts of corruption, that flag borrowers can was asked to be criminally responsible under Article 2 paragraph (1) of Law Number 31 of 1999 Jo. Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, so that it is not limited to corporate responsibility, even though it is a corporation that has signed a contract with the government